2014
DOI: 10.1116/1.4878215
|View full text |Cite
|
Sign up to set email alerts
|

Grafting titanium nitride surfaces with sodium styrene sulfonate thin films

Abstract: The importance of titanium nitride lies in its high hardness and its remarkable resistance to wear and corrosion, which has led to its use as a coating for the heads of hip prostheses, dental implants and dental surgery tools. However, the usefulness of titanium nitride coatings for biomedical applications could be significantly enhanced by modifying their surface with a bioactive polymer film. The main focus of the present work was to graft a bioactive poly(sodium styrene sulfonate) (pNaSS) thin film from tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…One way to understand this is the design of surfaces where chemistries are arranged in different patterns that create different topological cues to control cell adhesion and hence the downstream signaling. Previous studies have shown that patterns of click chemistry, 11 photolithography (by UV crosslinking), [18][19][20] and alkanethiol self-assembled monolayers (SAMs) 21,22 all directed cell adhesion and lineage specification. For example, adhesive sites spaced 34 or 62 nm apart directed mesenchymal stem cells (MSCs) to mature into osteoblasts or adipose cells, respectively.…”
Section: Surface Topography Of Bioactive Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to understand this is the design of surfaces where chemistries are arranged in different patterns that create different topological cues to control cell adhesion and hence the downstream signaling. Previous studies have shown that patterns of click chemistry, 11 photolithography (by UV crosslinking), [18][19][20] and alkanethiol self-assembled monolayers (SAMs) 21,22 all directed cell adhesion and lineage specification. For example, adhesive sites spaced 34 or 62 nm apart directed mesenchymal stem cells (MSCs) to mature into osteoblasts or adipose cells, respectively.…”
Section: Surface Topography Of Bioactive Materialsmentioning
confidence: 99%
“…Due to micro/nanoscale fabrication method advancements, breakthroughs in materials surface modification techniques, such as acidic treatment, 8,9 nitride coatings, [10][11][12] and selective laser melting, [13][14][15] have enabled the manufacture of microand nanoscale surface structured scaffolds that more closely simulate the in vivo environment of stem cells. 16 As a result, scaffolds used for regeneration have progressed from the passive distribution of stem cells and chemical agents to controllably ''smart'' scaffolds that actively direct tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%